The Experiences Of Minimal Access Surgery (Mas) In Gynecological Conditions - Huma Muzaffar; Aliya Waheed; Rubina Hussain (ziauddin University, 2024)
Background: Laparoscopic surgery is a minimal invasive procedure frequently used in recent years for diagnostic and therapeutic purpose. The aim of study is to highlight the role of Laparoscopy in acute or chronic gynecological conditions, findings and complication observed in the last three years in tertiary care hospital. Methods: All the cases of laparoscopy performed during Jan 2013-2016 at Department of Obs. & Gynae Ziauddin Hospitals were retrospectively analyzed. Results: Data of 167 patients were collected from medical record. In 27% cases diagnostic laparoscopy was done where as the remaining 73% cases had both the diagnostic as well as therapeutic procedures. The indications of laparoscopy were subfertility in 40 (23.9%) ,chronic pelvic pain in 73 (43.7%) and acute pelvic pain in 54(32.33%) cases. No major complication observed in this study. Laparoscopy was converted in to laparotomy in two patients due to massive adhesions and significant hemorrhage. Conclusion: Laparoscopy is a less invasive, safe and effective diagnostic as well as therapeutic procedure in different gynecological conditions. Key Words: MAS (Minimal Access Surgery), Minimal Invasive Surgery, Laparoscopy.